Effect of neonatal treatment with clomipramine on consummatory successive negative contrast - Ruetti, Eliana Martha (2013)
Neonatal administration of clomipramine (CLI) produces physiological, neuroendocrinal and behavioral abnormalities in rats when they reach adulthood, which are similar to those observed in animal models of depression. In consummatory successive negative contrast (cSNC), rats that have had experience drinking 32% sucrose solution drink significantly less 4% sucrose solution than rats that have drunk only 4% solution. It triggers an aversive-emotional reaction similar to fear or anxiety. We studied whether neonatal treatment with CLI alters the cSNC’s response in adult rats. The findings of the present work suggest that the neonatal treatment with an antidepressive could generate an increase tolerance to frustration in adult animals. CLI rats showed a faster recovery from the cSNC than control animals, which may be explained by an alteration of the HypothalamicPituitary-Adrenal axis (HPA), a serotonergic system deficit, a low expectative formation during pre-shift phase, or a combination of all these factors.